PEMBENTUKAN RUANG AKTIVITAS SOSIAL PADA RUANG TERBUKA PUBLIK TAMAN MENTERI SUPENO - Aggita Raras Putri; Eppy Yuliani; Boby Rahman (Universitas Islam Sultan Agung Semarang, 2017)
The Menteri Supeno Park is one of the grounds are among the active line meeting Menteri Supeno Street, Mugas Street and Pahlawan Street. A strategic location to the City Centre makes the Park is used for a variety of activities such as art, social activity, livelihoods, recreation and culture. The interconnectedness of activities in the public space is important to sustained beauty and tranquillity, let alone see the existence of the Park is located between the areas of trade, education and office. The Park has become one of the grounds which support the activity of the people as well as his role as the face of the image or the city of Semarang. See the conditions, then an attempt to examine and organize the Garden Store to see the Minister forms the social spaces that occur in the Park store is Minister. This, the future can be used as a reference for the review and recommendation of policy and development of the Park store is additionally the Minister so that the role and functions optimized.The research use descriptive qualitative approach to rationalistic Unitarians with supported research methods using the technique of place-centered behavior mapping. Research used variables i.e. system activity and the system places. On the collection of data using the techniques of field observation, interview and documentary studies in support of the information-related information of the writing of this research. Based on the analysis that has been done with regard to space activities forming the Park store is also influenced by the Minister several factors namely the interconnectedness of the store along with Minister of Garden spaces in it with the surrounding environment; accessibility and circulation; completeness of the complementary elements; Security; the ability of attracting visitors; view; climatology; and visitor activity. As for, the activity space formed by the need for customized visitor activity on the grounds that the new spaces were found in the garden at the beginning of the planning of the Park. As for the findings, activities outside the spaces of functions including the existence of visitors who utilize wifi facility to work on tasks in Open Space Theater, the presence of tenant builders toys in Space Playground, the existence of deviant behavior of the visitors on the space Sitting Group, the existence of the visitors who played badminton at the Plaza, the presence of hawkers and visitors who urinate in the Skatepark.Key Word: Public Open Space , Activity Space